Spatial characterization of backpropagating action potential-evoked Ca2+ signals in human cortical layer 2/3 pyramidal neurons - Szöts, Ildikó; Tóth, Martin; Ludányi, Csongor; Barzó, Pál; Csajbók, Éva Adrienn; Tamás, Gábor; Molnár, Gábor (Frontiers in Synaptic Neuroscience, 2026)
IntroductionIn pyramidal neurons, backpropagating action potentials (bAPs) activate voltage-gated calcium channels (VGCCs), producing compartment-specific dendritic Ca2+ transients. While extensively characterized in rodent models, little is known about the spatial properties and channel-specific contributions of bAP-induced Ca2+ signals in human cortical neurons.MethodsWe used simultaneous whole-cell patch-clamp recordings and two-photon Ca2+ imaging in acute human cortical slices to characterize bAP-evoked Ca2+ transients along the apical dendrites of layer 2/3 pyramidal neurons.ResultsWe found that Ca2+ signal amplitudes followed a non-linear spatial profile, increasing proximally and peaking between 50-100 µm from the soma before declining in more distal regions. Oblique dendrites exhibited significantly higher Ca2+ amplitudes compared to the primary apical branches. Morphological parameters, such as dendritic diameter, spine density, and branching, were correlated with the spatial profile of Ca2+ transients to the peak of the calcium signal profile. Pharmacological blockade of VGCCs revealed that major channel subtypes (L-, N-, R-, and T-type) contribute to dendritic Ca2+ influx, with distinct spatial effects. In particular, N-type channel blockade produced the largest attenuation in the medial dendritic segments, while T-type channel inhibition affected all regions.DiscussionThese findings highlight spatial heterogeneity and channel-specific contributions to dendritic Ca2+ signaling in human neocortical neurons and underscore the influence of dendritic morphology on signal propagation.